Late Roman fine pottery with stamped decoration discovered at (L?)ibida (Province of Scythia) - Mocanu, Marian (Rei Cretariae Romanae Fautorum Acta, 2012)
The Roman-Byzantine town of (L?)ibida is located in the province of Scythia, on the road linking Constantinopole with the Danubian Limes. the town was built in the early 4th century, during the reign of emperor Constantine the Great, and was abandoned in the early 7th century. Covering a fortified area of 24 hectares, the town is one of the largest in the region.